The role and mechanisms of matrix metalloproteinase-9 in peripheral neuropathic pain - Jia, Shuai Ying; Tang, Xiao-Jun; Su, Yao; Liu, Yu-Ning; Ming, Zhi; Lin, Jing-Yan (Frontiers in Molecular Neuroscience, 2025)
Peripheral neuropathic pain is a chronic, secondary pain state caused by damage or diseases of the peripheral nervous system, typically accompanied by edema, inflammatory responses, increased neuronal excitability, and glutamate accumulation. Matrix metalloproteinase-9 (MMP-9), an important enzyme, plays a key role in various physiological and pathological processes, primarily by degrading the extracellular matrix. Recent studies have shown that MMP-9 plays a crucial role in the onset and progression of central nervous system disorders, particularly neuropathic pain. This review discusses the mechanisms underlying the involvement of MMP-9 in various models of peripheral neuropathic pain, with the aim of exploring its potential as a therapeutic target.